THE INVARIANT ADAPTATION OF THE AIRCRAFT CONTROL SYSTEM IN EMERGENCY SITUATION DURING THE FLIGHT - Pavlova, Svitlana; Komar, Mykola (Proceedings of National Aviation University, 2016)
Purpose: The aim of this study is to develop a method for compensating the effects of failures of the aircraft automatic control system during the flight. Methods: This article reviews an approach based on the methods of theory of absolute nonlinear invariance. Results: In this paper, we present the example of a case of compensation of failure of the elevator with using the solution of the equation of the absolute invariance for pitch angle. Synthesis of automatic control device of aircraft orientation angles based on the analysis of the equations of the absolute nonlinear invariance is presented. Discussion: The use of the reconfiguration of the aircraft control system to ensure its survivability in flight is a perspective direction. However, the development of the concept of motion control of the aircraft with the use of the theory of absolute invariance will allow to realize an effective developed aircraft control method that will have advantages compared with the existing methods.